Evaluating the importance of metamorphism in the foundering of continental crust. Issue 1 (December 2017) - Chapman, Timothy; Clarke, Geoffrey; Piazolo, Sandra; Daczko, Nathan
Abstract The metamorphic conditions and mechanisms required to induce foundering in deep arc crust are assessed using an example of representative lower crust in SW New Zealand. Composite plutons of Cretaceous monzodiorite and gabbro were emplaced at 1.2 and 1.8 GPa are parts of the Western Fiordland Orthogneiss (WFO); examples of the plutons are tectonically juxtaposed along a structure that excised 25 km of crust. The 1.8 GPa Breaksea Orthogneiss includes suitably dense minor components (e.g. eclogite) capable of foundering at peak conditions. As the eclogite facies boundary has a positivedP/dT, cooling from supra-solidus conditions (T > 950 ºC) at high-P should be accompanied by omphacite and garnet growth. However, a high monzodioritic proportion and inefficient metamorphism in the Breaksea Orthogneiss resulted in its positive buoyancy and preservation. Metamorphic inefficiency and compositional relationships in the 1.2 GPa Malaspina Pluton meant it was never likely to have developed densities sufficiently high to founder. These relationships suggest that the deep arc crust must have primarily involved significant igneous accumulation of garnet–clinopyroxene (in proportions >75%). Crustal dismemberment with or without the development of extensional shear zones is proposed to have induced foundering of excised cumulate material atP > 1.2 GPa.